Girls’ empowerment through sports: Sports and physical activity with life skills - El Leithy, Weaam Mossallam Mohamed (AUC Knowledge Fountain, 2016)
Social norms, myths, and misconceptions negatively impact girls’ self-esteem, self-confidence and self-efficacy. These harmful traditions and social norms often cause feelings of inadequacy and powerlessness. With limited opportunities provided to girls, in general, and rural girls, in particular, including limitation of mobility and exclusion from education and employment, girls often lack self-esteem. This study focuses on rural marginalized girls in Upper Egypt, which is a conservative setting characterized with harmful social norms and practices; such as, early marriage and female genital mutilation/cutting (FGM/C). This thesis examines rural girls’ empowerment through sports and physical activities and argues that sports and play are rights through which other rights can be addressed. Sports and physical activities are innovative approaches that can bring about self-reliance, self-esteem, and self-efficacy, which ultimately promote girls’ empowerment. In this respect, the study provides an analysis of UNICEF Egypt’s Sports for Development Project (S4D) namely Sports and Physical Activities with Life Skills. The project was implemented in Assiut governorate in collaboration with Assiut Childhood and Development Association (ACDA), and the Ministry of Education (MoE) Directorate in Assiut governorate. The S4D project was piloted in 50 community schools in three rural districts; namely, Abnoub, El Fath, and Dayrout during the academic year 2013-2014. The analysis was undertaken in light of the three main components of the empowerment theory, which are: the intrapersonal, the interactional and the behavioral. The results of the analysis revealed that sports and physical activities with life skills can promote girls’ empowerment and enhance their school attendance and hence retain them in education. The analysis also revealed that even though sports and physical activities are effective innovative approaches, their deployment in development interventions has been overlooked by the development organizations. Most of the development interventions tend to adopt complex approaches, thus pay less attention to simple and entertaining approaches such as sports and physical activities. Consequently, there is a need to promote the use of sports as a right and as a crosscutting strategy to address other rights.